THU0724-HPR Self-management exercise program associated to spa therapy increased the physical activity level of people with symptomatic knee osteoarthritis: a quasi-randomized controlled trial. (15th June 2017) - Gay, C; Auclair, C; Boisseau, N; Gerbaud, L; Coudeyre, E
Abstract : Background: Treating knee osteoarthritis (OA) in the medical phase is today well standardized. Guideline orientated approaches aiming at increasing physical activity (PA), improving pain and disability. Objectives: To assess effectiveness of self-management exercise program associated to spa therapy at 3 month on the improvement of physical activity (PA) level, disability, pain, anxiety, fears and believes in symptomatic knee osteoarthritis people. Methods: Prospective, multicentric, quasi-randomized controlled trial with alternate month design method (one month periods). People with symptomatic knee OA people (stage I-IV, Kelgren and Lawrence scale) with low and moderate PA level were included in 3 spa therapy resorts. Intervention group (IG) received 5 self-management exercise sessions (1h30; education, aerobic, strength training, range of motion) + information booklet + 18 sessions (1h) of conventional spa therapy (STC). Control group (CG) received information booklet + 18 sessions of STC. The primary outcome was changes at 3 months in PA level (IPAQ short form score) and secondary outcomes were WOMAC function, pain (VAS), HAD anxiety/depression, KOFBeQ fears and believes changes. Results: 131 subjects were included. The mean age was 65.6 years [± 6.7]. WOMAC function score was 22.1/68 [±11.3] and pain was 4.6/10 [± 1.9] at inclusion. Both groups significantly increased PA level measured with continuous IPAQ total score (MET-minutes/weeks), with superiority for IG (+77.8%; p=0.0062) than CG (+50.7%; p=0.0099). There was no change in setting time. Disability (-11.3%; p=0.0370) and pain (-15.2%; p=0.0032) also decreased significantly for both groups. Anxiety (-11.6%; p=0.0195) and fears and believes (-18.2%; p=0.0146) decreased significantly only in intervention group. Other data will be presented later. Conclusions: This study confirms the impact of STC on disability and pain and gives news data's on physical activity level. Self-management exercise program improve anxiety, fears and believes. Complex educational strategies comprising information booklet with or without self-management exercise program can be proposed and adapted to OA phenotypes. References: Fernandes, Linda, Kåre B. Hagen, Johannes W. J. Bijlsma, Oyvor Andreassen, Pia Christensen, Philip G. Conaghan, Michael Doherty, et al. EULAR Recommendations for the Non-Pharmacological Core Management of Hip and Knee Osteoarthritis. Annals of the Rheumatic Diseases 72, no. 7 (July 2013): 1125–35. Gay, C., A. Chabaud, E. Guilley, and E. Coudeyre. Educating Patients about the Benefits of Physical Activity and Exercise for Their Hip and Knee Osteoarthritis. Systematic Literature Review. Annals of Physical and Rehabilitation Medicine 59, no. 3 (June 2016): 174–83. Disclosure of Interest: None declared